Model Development of Non-Destructive Coffee Beans Moisture Content Determination Using Modified Near Infrared Spectroscopy Instrument - Rizky Wiradinata; I Wayan Budiastra; Slamet Widodo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
A method of non-destructively moisture content measurement of coffee beans is using near infrared spectroscopy (NIRS) which in general can be applied to determine chemical content of various organic materials. However, the commercial NIR instrument can not measure many samples in a single time, consequently the faster measurement can not be realized. The purposes of this research was to study the performance of modified NIR instrument prototype for measuring the moisture content of Java Preanger coffee beans. Performance study of modified NIR instrument was carried out on 50 coffee bean samples for determination of sample moisture content. The reflectance spectra of samples were measured bymodified NIRS instrument and then water content of samples was determined by oven method. The spectra data and water content were calibrated by multiple linier regression method to find the best calibration model. The result of this research show that number of wavelengths chosen to predict the moisture contentof Java Preanger coffee bean accurately is 17 wavelengths. The correlation coefficient (R) moisture content based on NIRS instrument and oven method was 0.902, this suggest that the model is able to explain 90.2% the diversity of existing data. The value of standard error calibration (SEC) and standard error prediction (SEP)was almost zero meaning that the error of prediction is low. This study also reveal that the value of residual predictive deviation (RPD) is 2.32, which means the prediction model for determination of Java Preanger coffee beans moisture content is good enough.